2000
DOI: 10.1016/s0022-5223(00)70126-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against a pivotal role of preformed antibodies in delayed rejection of a guinea pig–to–rat heart xenograft

Abstract: These findings argue against a pivotal role of preformed xenoantibodies in the pathomechanistic process of delayed xenograft rejection and challenge the therapeutic strategy to reduce preformed xenoantibody levels before xenotransplantation in complement-inactivated recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…24,25 There were many studies for natural antibodies in the field of xenografts, and it was revealed that transplantation of un-related tissues induces a rapid increase of serum IgM and a subsequent increase of serum IgG. 26,27 Similar results were observed in serum IgM and IgG levels after implantation of X-grafts in this study. We thought that xenologous fibrin coating of vascular prostheses reacted with natural antibodies as antigens expressed on unrelated tissues.…”
Section: Discussionsupporting
confidence: 81%
“…24,25 There were many studies for natural antibodies in the field of xenografts, and it was revealed that transplantation of un-related tissues induces a rapid increase of serum IgM and a subsequent increase of serum IgG. 26,27 Similar results were observed in serum IgM and IgG levels after implantation of X-grafts in this study. We thought that xenologous fibrin coating of vascular prostheses reacted with natural antibodies as antigens expressed on unrelated tissues.…”
Section: Discussionsupporting
confidence: 81%
“…The subject was reviewed by Fox and Harrison [30]. Grimm and colleagues published evidence indicating that antibodies may not be critical in delayed rejection of guinea pig‐to‐rat heart xenografts [31]. On the other hand, Salvaris and colleagues, working with d'Apice, described the role of naturally acquired anti‐gal antibodies in gal‐knockout mice in causing a form of allograft rejection that is similar to DXR/AVR [32].…”
Section: Delayed Xenograft/acute Vascular Rejection (Accelerated Rejementioning
confidence: 99%
“…CVF acts as a homolog of C3 in vivo ,16) and administration to recipient before transplantation can suppress graft rejection by depleting the complement system in advance 17-19). Several studies concluded that CVF administration before xenotransplantation prolonged graft survival 20)21). To ascertain the effects of the aforementioned on xenoperfused porcine myocardium, we evaluated basic laboratory outcomes, such as complete blood cell counts (CBC), arterial blood gas analysis (ABGA), and evaluated myocardial cell injury by measuring creatine kinase-MB (CK-MB) and Troponin I.…”
Section: Introductionmentioning
confidence: 99%